AUDIT TOOL AND LINKED ARCHIVE SYSTEM (ATLAS) IN IMPROVING AUDIT QUALITY - Krisis Ayu Margaret; Novita Novita; Aditya Fadillah Azka (Applied Accounting and Management Review (AAMAR), 2023)
This study aims to determine the use of the Audit Tool and Linked Archive System (ATLAS) Application as a working paper in improving audit quality. The population of this study is auditors who work in public accounting firms where the number is not known for sure so that from the results of calculations with a sample formula for an unlimited population, a minimum number of samples of 96 samples was obtained. In this study, the samples processed were 100 collected from the results of questionnaire answers that were distributed online to auditors working in public accountants with auditor criteria who had applied the use of the ATLAS Application in the audit process. The data analysis technique used is with PLS (Partial Least Square). The results of the study show that the ATLAS application plays an important role in improving the quality of audits. The auditor who was sampled in this study stated that the ATLAS Application provides a structured working paper that is very helpful for auditors in carrying out audit procedures starting from the planning stage, risk response to the audit reporting stage in accordance with audit standards as a basis for providing audit opinions where these stages help auditors in improving audit quality. Furthermore, the use of the ATLAS Application in the implementation of audit procedures makes the audit process more effective and efficient.